Patterns of physical performance spurts during adolescence: a cross-cultural study of Canadian, Brazilian and Portuguese boys - Guimarães, Eduardo (2021)
Background: Data relating physical performance to the timing of the adolescent growth spurt are lim ited. Aim: This study identifies: (i) age-at-peak height velocity (APHV), (ii) physical performance spurt patterns aligned to APHV; and (iii) cross-cultural and time patterns in Canadian, Brazilian and Portuguese boys. Subjects and methods: A total of 512 boys (131 Canadian, 250 Portuguese and 131 Brazilian), 8–17 years of age were followed serially using longitudinal data. APHV was identified and five physical performance measures velocities [trunk extension (TE), trunk flexion (TF), standing long jump (SLJ), curl-ups (CU) and handgrip strength (HG)] were aligned at 6-month intervals, 4 years around the attainment of PHV. Velocities were estimated using a non-smooth mathematical procedure. Results: APHV was 13.9 ± 1.0, 13.4 ± 1.6 and 13.0 ± 0.8 years for Canadian, Brazilian and Portuguese boys, respectively. Maximal velocity in SLJ was attained between 12 and 6 months prior to PHV. For HG, peaks were attained 12–24 months after PHV. Maximal velocity in TE occurred between 12 and 0 months prior to PHV, while CU peaked between PHV and 6 months after PHV. Conclusion: Patterns of spurts in physical performance have remained relatively the same and do not appear to be influ enced by cross-cultural differences.